The Role of Sensorimotor Difficulties in Autism Spectrum Conditions - Hannant, Penelope; Tavassoli, Teresa; Cassidy, Sarah (Frontiers in Neurology, 2016)
Abstract In addition to difficulties in social communication, current diagnostic criteria for autism spectrum conditions (ASC) also incorporate sensorimotor difficulties; repetitive motor movements and atypical reactivity to sensory input (APA, 2013). This paper explores whether sensorimotor difficulties are associated with the development and maintenance of symptoms in ASC. Firstly, studies have shown difficulties coordinating sensory input into planning and executing movement effectively in ASC. Secondly, studies have shown associations between sensory reactivity and motor coordination with core ASC symptoms, suggesting these areas each strongly influence the development of social and communication skills. Thirdly, studies have begun to demonstrate that sensorimotor difficulties in ASC could account for reduced social attention early in development, with a cascading effect on later social, communicative and emotional development. These results suggest that sensorimotor difficulties not only contribute to non-social difficulties such as narrow circumscribed interests, but also to the development of social behaviours such as effectively coordinating eye contact with speech and gesture, interpreting others’ behaviour and responding appropriately. Further research is needed to explore the link between sensory and motor difficulties in ASC, and their contribution to the development and maintenance of ASC.